IgG, IgM, and IgA Antinuclear Antibodies in Discoid and Systemic Lupus Erythematosus Patients - Sheridan A. Jost; Lin-Chiang Tseng; Loderick A. Matthews; Rebecca Vasquez; Song Zhang; Kim B. Yancey; Benjamin F. Chong (The Scientific World Journal)
IgG antinuclear antibodies (ANAs) are elevated in patients with systemic lupus erythematosus (SLE) compared with patients with discoid lupus erythematosus (DLE). To provide an expanded immunologic view of circulating ANAs in lupus patients, we compared the expressions of IgG, IgM, and IgA ANAs in DLE and SLE patients. In this cross-sectional study, sera from age-, gender-, and ethnic-matched SLE N=35, DLE N=23, and normal patients N=22 were tested for IgG, IgM, and IgA ANAs using enzyme-linked immunosorbent assays (ELISAs) and indirect immunofluorescence (IIF) with monkey esophagus as substrate. ELISAs showed elevated levels of IgG ANA, IgM ANA, and IgG/IgM ANA ratios in SLE patients compared with DLE and normal patients. IgA ANA expression was higher in SLE and DLE patients versus normal patients. IIF studies showed higher percentages of patients positive for IgG, IgM, and IgA ANAs in the SLE group. Higher IgG/IgM ANA ratios in SLE than DLE show enhanced class-switching and a more sustained humoral response in SLE. They also suggest a potential connection of IgM ANAs with disease containment.